Generation of highly stable electron beam via the control of hydrodynamic instability - Yan-Jun Gu; Zhan Jin; Zhen-Zhe Lei; Shingo Sato; Kai Huang; Nobuhiko Nakanii; Izuru Daito; Masaki Kando; Tomonao Hosokai (Scientific Reports)
Abstract By employing the stabilizer in the supersonic gas nozzle to produce the plasma density profile with a sharp downramp, we have experimentally demonstrated highly stable electron beam acceleration based on the shock injection mechanism in laser wakefield acceleration with the use of a compact Ti:sapphire laser. A quasi-monoenergetic electron beam with a peak energy of 315 MeV ± 12.5 MeV per shot is generated. The electron pointing fluctuations are less than 1 mrad, which is a significant improvement over previous results. This is due to the precise control of the target density distribution and the relative distance between the shock and the laser focal position. The Particle-in-cell simulations demonstrate the sensitivity of electron acceleration to the target profile, while the computational fluid dynamics prove the stabilizer’s effect on gas formation. Further developments of this scheme have the potential to deliver a high repetition rate gas target. The corresponding reproducibility of the accelerated electron beam paves the way for the realisation of compact laser plasma accelerators and the potential application of free electron lasers.